Patient Care for Gout Arthritis with Physical Mobility Impairments Who Received Active Therapy Range of Motion (ROM) at Kandangsapi Health Center - Risa Lailatul Afita; Bagus Dwi Cahyono; Evy Aristawati (KHD Production, 2024)
Impaired physical mobility is a health problem where a person cannot move freely and regularly. In general, the problem of impaired physical mobility can occur in various age groups, one of which can occur in elderly sufferers. gout arthritis. Generally, sufferers of gout arthritis experience joint stiffness and pain when moved, making it difficult for sufferers to move their extremities. If physical mobility problems are not treated immediately, it can cause sufferers to have difficulty carrying out daily activities. Generally, sufferers of gout arthritis take medication to lower uric acid levels, but consuming too much medication can cause dependence, memory problems, kidney failure, and so on. Therapy range of motion can be a reference for overcoming physical mobility disorders that can be done anytime, anywhere, and do not cause side effects such as taking drugs. This case study aims to identify further changes in physical mobility experienced by sufferers of gout arthritis who experience physical mobility problems after therapy range of motion. This research method is a case study design where the patient is approached using the nursing process. In this case study, the author applies the therapy range of motion active in-patient Mrs. S for seven days. The results showed that on the seventh day, the nursing problem of impaired physical mobility was resolved, and this was proven by achieving all the outcome criteria for nursing goals. So, the therapy range of motion effectively overcame physical mobility disorders in patients with gout arthritis.